Detection and Enumeration of the Commonest Stool Parasites Seen in a Tertiary Care Center in South India. (23rd June 2013) - Chandrashekar, Vani
Abstract : The aim of this study was to identify common stool parasites in patients attending a tertiary care centre in South India. We evaluated 2355 stool samples and parasites were detected in 7.9% of samples. 41.1% of our patients were in the 45–58-year age group. Protozoal infections were the commonest seen in 7.8% of samples. Entamoeba histolytica was the commonest protozoa (4.6%) followed by Entamoeba coli (1.2%) and Giardia (0.8%). Entamoeba histolytica and Entamoeba coli were together seen in 0.63%, and they were the commonest organisms seen in samples with multiple-organism infection. Both were equally detected in diarrheal samples.